(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Makalah Pursuant to the Fourteenth Schedule (Section 5A) of the National Land Code 1965 (NLC), in the Computerized Land Registration System (CLRS), land situated under the Registry titles or Land Office title is in two forms, namely; the computer printed register document of title which is kept in the land office while the computer printed issue document of title is given to the proprietor of land where he may at any time apply for conversion of an existing issue document of title to a computer printed issue document of title by lodging the existing issue document of title at the land Registry. Pursuant to Paragraph 8(5) of the Fourteenth Schedule of the NLC, the Registrar has the discretion to convert the existing issue document of title without there being an application made by the proprietor of land. With this title, the proprietor will acquire the indefeasibility of title to the land and is entitled to subdivide, amalgamate and partition the land, and can enter into deaingls on that land, for example transfer, charge and lease. Based on the case analysis method used in decided cases on the theft of information in CLRS, this article intends to analyse the extent of the security of the computerized land registration system in protecting the ownership of land proprietors. The findings show that there is fraud and theft of information in the CLRS of the land office. The solutions offered by Islamic law are also considered in order to protect the property rights of parties involved. Keywords: Computerized land Registration system, theft of information, solutions